Top Differential Diagnosis Should Be Microscopic Polyangiitis in ANCA-Positive Patient with Diffuse Pulmonary Hemorrhage and Hemosiderosis - Nicholas D. Ward; Diane E. Cosner; Colleen A. Lamb; Wei Li; Jacqueline K. Macknis; Michele T. Rooney; Ping L. Zhang (Case Reports in Pathology)
A rat model of antineutrophil cytoplasmic antibody (ANCA) associated vasculitides reveals crescentic glomerulonephritis as seen in human renal biopsies and diffuse lung hemorrhage that is not well documented in human lung biopsies. A 64-year-old male, with shortness of breath and mild elevation of serum creatinine, was found to have a positive serum test for ANCA, but negative antiglomerular basement membrane antibody. A renal biopsy showed pauci-immune type of crescentic glomerulonephritis and focal arteritis. The prior lung wedge biopsy was retrospectively reviewed to show diffuse hemorrhage and hemosiderosis with focal giant cells. In addition, small arteries revealed subtle neutrophil aggregation, and margination along vascular endothelium, but no definitive vasculitis. The pathology of ANCA associated vasculitides results from activated neutrophils by ANCA and subsequent activation of the alternative complement cascade with endothelial injury, neutrophil aggregation and margination. Our findings, after the correlation between lung biopsy and renal biopsy, imply that the top differential diagnosis in the lung biopsy should be microscopic polyangiitis when diffuse pulmonary hemorrhage and hemosiderosis are present in this ANCA-positive patient.